If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = 48 Reorder the terms: 3(3 + 2x) = 48 (3 * 3 + 2x * 3) = 48 (9 + 6x) = 48 Solving 9 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 6x = 48 + -9 Combine like terms: 9 + -9 = 0 0 + 6x = 48 + -9 6x = 48 + -9 Combine like terms: 48 + -9 = 39 6x = 39 Divide each side by '6'. x = 6.5 Simplifying x = 6.5
| 5.8(x-1)=-0.2x+42.2 | | 125=x-9 | | 5x+40=15 | | -144x^2+100=0 | | 9(x+2)+2(x+2)=6x-6 | | 46-3n=-27 | | 3(2x-4)-2(5x-1)= | | 2x^5(x-x^2+6x^3)= | | 38-10n=-3(n-8) | | 2x^5(x-t^2+6t^3)= | | -4a+5+2a-9=44 | | 13x-15=x-5 | | f(x)=8x^3-2x^2-15x | | 13m+2=4m+110 | | 7b^2+23b+6=0 | | 4x*33y= | | 4d+d+3d= | | f(x)=x^5-x^4+8x^3-8x^2+15x-15 | | r=0.155 | | (v+6)=2v^2+6v+29 | | n+3n-2n=168 | | f(x)=x^4+10x^2+9 | | 8-3t=17-2t | | 8a-4=5a+47 | | 0=-3x^3+24x^2+27x | | 5x^2-20x+24=0 | | 24+4y-1=14y-12-3y | | 2p+4(m-6+2m)-12m+3p= | | 4n+3=3n-5 | | 4x^3+28x^2=-8x^2-56x | | n+37=5(n+1) | | 35x+7y=-18 |